The Effect of Electronic Modules Based on Problem-Based Learning on Creative Thinking Ability - Fahrul Juanda; Festiyed Festiyed (Physics Learning and Education, 2023)
Learning models proposed by an independent curriculum and student-centered tools have not been fully utilized. This observation is supported by the outcome of an initial assessment, which revealed a low level of creative thinking ability among students. This initial assessment forms the foundation for the research problem addressed in the context of electronic module-based problem learning in physics education. The study employs a quasi-experimental design utilizing a Randomized Control Group Only Design and posttest-only methodology. Data collection solely involves knowledge-related aspects. In this study, the experimental group underwent treatment through the utilization of problem-based learning electronic modules, while the control group did not receive this treatment. The research findings indicate notable variations in student creativity thinking abilities, discernible through the diverse average scores in each group's student responses. Assessments included tests for normality, homogeneity, and a two-sample similarity test. The analysis results indicate that the value of "th" falls within the range of H0 resistance, leading to the acceptance of H1 at a significance level of 0.05. Statistical analysis of the data demonstrates that th > tt is 2.6318 > 2.0181. Consequently, it can be inferred that disparities exist in student creativity thinking skills concerning knowledge acquisition when comparing the utilization of problem-based learning electronic modules to its non-utilization.